Sodišču pridružena mediacija v individualnih delovnih sporih - Cankar, Nataša (Podjetje in delo, 2023)
The main focus of the article is court-annexed mediation in individual labour disputes in Slovenia. The aim is to describe the current state of affairs in this legal field. The beginnings of court-annexed mediation in Slovenia are described first, followed by the existing legal documents that serve as foundation for the existing court-annexed mediation, the main attributes of mediation in general and the particulars of mediation in individual legal disputes, including the current case law. The second part of the article lists the types of individual labour disputes that are most commonly found in court-annexed mediation as well as some as of yet unsolved legal dilemmas in this particular field. The third part of the article includes statistical data of individual labour disputes, taken from the judicial statistics, followed by the judicial statistics of court-annexed mediation in Slovenia. The author suggests which subjects should be focused on first to further develop the mediation in individual labour disputes. Mediation in Slovenia is primarily practised as court-annexed mediation, but the aim for the future should be the development of workplace mediation. This type of mediation could significantly contribute to the prevention of individual labour disputes as well as lessen the number of cases that have to be solved in a court of justice.
Keywords: delovna razmerja; delovni spor; delovno pravo; Mediacija; odpoved; sodišča; sodni spor